Can Mathematics and Computational Modeling Help Treat Deep Tissue Injuries? - Vermolen, Fred (Adv Wound Care (New Rochelle), 2019)
Objective: Improving the treatment of deep tissue injuries, such as burns, by the use of computational modeling, instead of by animal experiments. Approach: Development of mathematical relations between various parameters and processes. Furthermore, solving the resulting problems through the use of numerical methods, such as finite-element methods. Results: Using our framework, we are able to simulate wound contraction in two dimensions, in which the wound area is followed over time. Our studies indicate that the degree of contraction can be reduced if the appearance of myofibroblasts is inhibited and if their apoptosis is enhanced. Furthermore, after skin grafting, splinting procedures are to be continued as long as TG-beta like growth factor levels are significant. Innovation: A morphoelasticity-based and computational–probabilistic framework for studying the evolution of burn injuries. Conclusion: The current framework is able to reproduce the time evolution of the wound area as observed in clinical results for skin grafts.